Analisa Struktur Mikro dan Kekuatan Bending Sambungan Las TIG dengan Perbedaan Kuat Arus Listrik pada Logam Tak Sejenis Aluminium Paduan 5052-Baja Galvanis dengan Filler Al-Si 4043 - Bintarto, Redi; Widodo, Teguh Dwi; Raharjo, Rudianto; Dewi, Francisca Gayuh Utami; Pratama, Gesha Denny; Ma’arif, Moh. Syamsul (Jurnal Rekayasa Mesin, 2020)
This study aims to determine the various effect of heat input due to varied electric current on microstructure of the weld joints and the bending strength of 2 dissimilar metals (aluminum alloy 5052 and galvanized steel) with Al-Si 4043 as filler. This experimental research was worked out by varying the strength of the current which can then be calculated into a heat input. The current inputs applied were 30.8 J / mm (70A), 35.2 J / mm (80A) and 39.6 J / mm (90A) while the protective gas flow rate used is 14 liters / minute. This study showed that the increase in heat input greatly affects the shape of the weld area microstructure, i.e. the microstructure and bending strength. Greater heat input due to higher current can melt larger area, so that the join process occured better. The highest bending strength at 9.05 Mpa was achieved for heat input at 39.6 J / mm or strong current of 90 A. The weakest bending strength at 8.88 Mpa was achieved for heat input at 35.2 J / mm or a strong current of 70 A.